Erratum: HER2/p53 ratios among canine mammary tumours and respective derived cell culture (Multidisciplinary Science Journal DOI: 10.29327/multiscience.2022001) - Sakamoto, Silmara Sanae; Panegossi, Letícia Colin [UNESP]; De Carvalho, Roberto Gameiro [UNESP]; Cardoso, Tereza Cristina [UNESP] (Malque Publishing, 2023)
The article was originally published with two missing author names and incorrect author name sequencing. This erratum aims to correct the original paper, which has been updated:.